The study on Morphological, Phytochemical and Pharmacological aspects of Rhinacanthus nasutus. (L) Kurz (A Review) - Suman Bukke, Raghu PS, Sailaja G, Thyaga Raju Kedam (Journal of Applied Pharmaceutical Science)
The present review provides an account of the knowledge on the morphology, phytochemistry and pharmacological aspects of Rhinacanthus nasutus R Kurtz. This plant also called Nagamalli is a perennial shrub growing to 60-76 cm in height with tender stem. A wide range of chemical compounds have been isolated, mainly flavonoids, benzenoids, coumarin, anthraquinone, quinone, glycosides, carbohydrate, triterpenes, sterols, anthraquinones, napthoquinones. Different parts of plant have been used in folk medicine for treating liver disorders, skin diseases, peptic ulcers, helminthiasis, scurvy, inflammation and obesity. The napthoquinones known as rhinacanthin-C and rhinacanthin-D, extracted from the R.nasutus are reported to have anti-inflammatory and analgesic activity. The promising alkaloid, Rhinacanthin isolated from R.nasutus having antibacterial and antihelmintic activity. R.nasutus shows several other characteristic pharmacological effects like platelet aggregation inhibitor, antidiabetic, antituberculosis, anticancer which are consistent with the reported uses of the plant extracts in the indigenous system of medicine. Further the leaves of this plant are used in the preparation of shampoos or detergents. Hence the present article includes the detailed exploration of morphology, phytochemistry, and pharmacological aspects of R.nasutus in an attempt to provide a direction for further research.
Keywords: Rhinocanthus, Pharmaceutical uses, medicinal compounds, rhinocanthecins.